Implementing Flipped Classroom to Enhance Reading Achievement: A Comparative Study on Female and Male Students - Purwanti, Endah; Rudi Hartono; Kathrina Rustipa (English Education Journal, 2024)
This study aimed to examine the impact of the flipped classroom method on students' reading achievement, focusing on comparing its effectiveness between female and male students. A mixed-method research design was used, incorporating both qualitative and quantitative methods. The participants were 28 second-grade social science (IPS) students (14 males and 14 females) during the 2023-2024 academic year. Data collection methods included pre-and post-tests, as well as semi-structured interviews. The findings revealed that the flipped classroom method significantly improved reading achievement for both genders. Based on the results obtained, from these two genders, the most specifically experienced a change in grades were female students. In female students at the beginning before applying to flipped classrooms, their reading scores ranged from 70 to 80, then improved to a range of 78 to 88. Meanwhile, the male students also changed their scores, ranging from 64 to 76, then improved to 70 to 86. The use of flipped classrooms showed a greater benefit to the students. Female students demonstrated higher engagement, collaboration, and enjoyment levels, resulting in better overall performance in reading tasks. In contrast, male students also experienced improvement but faced more difficulties in maintaining their focus, so their grades did not improve too much. Apart from having an impact on students' reading results, it also made male and female students active and enthusiastic in the class. Besides, it is effective to make the students enjoy the learning process and not feel bored with the monotonous learning style. This insight contributes to the field by highlighting the importance of gender-specific adaptations in flipped classroom strategies to enhance reading instruction for all students.